The Role of Healthy Villages in Inclusivity of Disabilities and the Elderly: Peran Kalurahan Sehat Dalam Inklusifitas Disabilitas dan Lansia - Surwanti, Arni; Puspitosari, Warih Andan; Purnama Asri, Retno Wudowati (Universitas Lancang Kuning, 2025)
The problem that will be solved is: Girimulyo Village is one of the villages in Gunungkidul Regency where there have been suicide cases., There are three factors behind it, namely health, social, and economic problems. This Community Partnership Empowerment Program seeks solutions to problems by using the role of Healthy Villages to ensure the realization of inclusion in the elderly and disabilities in the Social, Health, and Economic fields. The methodology used is to strengthen Healthy Village cadres to carry out programs to overcome health, social and economic problems. In this Community Partnership Empowerment Program, there are outputs such as increasing the capacity of data collection, there is data on sorting out disabilities and the elderly in the village, there is an assessment of the needs of the disabled and the elderly, there is an increase in the capacity of Healthy Village cadres in providing services, there are operational standards of service procedures, there are additional skills in processed foods made from fish and moqf and knowledge of entrepreneurship and business management for representatives of people with disabilities, and the elderly and healthy village cadres. The role of the Healthy Village Team as in Girimulyo Village is very important in ensuring that people with disabilities and the elderly get attention, therefore in other villages organizations like this are very necessary and of course their role needs to be strengthened by being equipped with knowledge and skills and village funding support for the implementation of their activities.